EPÍTOME ANALÍTICO DE LA POLÍTICA PÚBLICA DE ADOLESCENCIA EN TUNJA (2016)
This study aims to determine the impact of public policies on adolescent substance abuse made in the municipal development plan “Acts of truth” more humane 2012-2015 Tunja, Healthy, safe and sustainable by analyzing the guidelines and the strategies set out in the policies to reduce legal and illegal psychoactive substances. The results indicate an improvement in the formulation of strategies that affect  macro and micro social and personal factors, the holistic view of public issues determines the need to prevent and avoid the use and abuse of SPA, to mitigate the damage and overcome the bad situation especially in children. The lack of responsiveness, resources, surveillance and monitoring has a negative impact on the effectiveness of public policies and the guarantee of fundamental rights in adolescents.